P06.02.B Advanced CAR-T cell against orthotopic glioblastoma mouse model. (5th September 2022) - Hwang, K; Nam, K M; Kwon, J E; Ji, S Y; Han, J H; Seo, T W; Choi, Y N; Kim, K; Jeon, S; Choi, K; Kong, S; Kim, C Y
Abstract: Background: The adoptive and engineered chimeric antigen receptor (CAR) T cells have demonstrated remarkable success in treating hematologic cancers; however, this success has yet to be extrapolated to solid tumors such as glioblastoma multiforme (GBM). The purpose of this study was to evaluate the survival efficacy using advanced CAR-T cells in orthotopic GBM mouse model. Material and Methods: Advanced CAR-T cell, which reprograms the patient's T-cells with a transgene encoding part of interleukin-7 receptor-α (ΔIL7Rα) domain in addition to the CD3ζ signaling domain and 4-1BB costimulatory domain in the advanced CAR gene to exhibit excellent in vivo persistence and anti-tumor effect of advanced CAR-T cells. In addition to the advanced CAR gene, TGF-beta converter is introduced, which converts the inhibitory signal of TGF-beta, an immunosuppressive cytokine overexpressed in the hostile tumor microenvironment, into the activation signal of the cytokine IL-18 in advanced CAR-T cells.DAY9 NSG mice bearing orthotopically xenografted GBM cell lines (1 × 10 5 U251MG expressing IL13Rα2) were randomized to 8 experimental groups. Each experimental group was intravenously injected with only once with different subtype advanced CAR-T cells (Td ~ 47.3% of 5 × 10 6 ) and monitored for survival. Results: Among treatment groups, mice treated with advanced CAR-T cells of TGF-β converter subtype demonstrated a statistically significant increase in survival (p=0.042, 95%CI, 0.375-0.981) compared with other subtypes. In DAY9 orthotopic GBM mouse model, we showed that a single I.V. injection of advanced CAR-T cells targeting IL13Rα2-specific tumor achieved survival benefit. Conclusion: This study is the first report to show statistically significant survival benefit in DAY9 orthotopic GBM mouse model using a single I.V. injection of advanced CAR-T cells, yet merits further clinical trials in real world of clinical setting.